Changes in the total polyphenolic content and antioxidant activity of fermented Morinda citrifolia L. - Chaiyavat Chaiyasut (2018)
© 2018 The Authors. Objective: The fermented plant beverages (FPBs) are considered as functional food. A detailed scientific investigation is required to develop functionally potential FPBs. The present study aimed to investigate the changes in total phenolic content and antioxidant properties of Lactobacillus paracasei HII01-mediated fermented Morinda citrifolia L. (noni) juice. Methods: The fermentation media consist of 3:10:1 ratio of noni, water, and carbon source (either cane sugar or honey) along with 10% of inoculum (L. paracasei). The control samples were prepared without inoculum or substrate. The variations in pH, acidity, total phenolic content, and the antioxidant capacity of the samples were kinetically measured by standard methods. Results: The pH and total acidity of the samples were progressively reduced and improved when the duration of fermentation was prolonged, respectively. After 15 days of fermentation, F1 (1.198 mg GAE/ml sample) and F3 (1.265 mg GAE/ml sample) exhibited high total phenolic compound compared to other samples. Likewise, sample F3 displayed maximum antioxidant capacity. The samples with cane sugar exhibited high phenolic content, free radical scavenging activity, and chelating power than samples with honey. Conclusion: About 15 days of fermentation in sufficient to obtain the high quality (rich in phenolic compounds and antioxidant capacity) fermented M. citrifolia juice using L. paracasei, and cane sugar as starter, and carbon source, respectively.